Implementasi Metode Aras Dalam Pengambilan Keputusan Untuk Pemilihan Inseminator Terbaik - Gunawan Rambe, Ari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The success of inseminator officers is largely determined by the synergy of the roles and functions of each work unit at the Puskeswan Kota Subulussalam, as well as the activities of technical officers in the field. The role of inseminator officers is one of the main factors in the success of the program as measured by pregnancy and birth rates. Puskeswan, namely the Animal Health Center which provides services in the field of animal health in Subulussalam. The problem that occurs at the Subulussalam Health Center every year is to select the best inseminators to increase the appreciation of the performance of the inseminators, in selecting the best inseminators. still less effective. To overcome this problem, the authors want to select the best inseminator by implementing a decision support system by applying the ARAS method because this method is used for ranking so that the problem is more focused because it is based on predetermined criteria and weight values ​​so that it will get maximum results and produce better decisions. accurate in selecting the best inseminator at the Subulussalam Health Center